Death is Served The Serialization of Death and Its Conceptualization Through Food Metaphors in US Literature and Media - Castelli, Stella (American Culture Studies, 2023)
The American cultural imaginary is hungry for death, and thus representations of death are prominently repeated and serialized in US literature and media. Stella Castelli shows how American culture fetishizes death as part of a repetition compulsion which stems from the inability of language to satisfactorily grasp death. Taking an intermedial approach, she investigates the forms and tropes born from this preoccupation with death and conceptualizes its imagination alongside an appetite which manifests as repetitive encoding. These metaphors of food consumption provide a hermeneutic framing for analyzing representations of death across American literature and media.